Experimental investigation on impact and bending properties of a novel dactyl-inspired sandwich honeycomb with carbon fiber. (30th August 2020) - Han, Qigang; Qin, Hanlin; Liu, Zhanhang; Han, Zhiwu; Zhang, Junqiu; Niu, Shichao; Zhang, Wenqiang; Sun, Yanbiao; Shi, Shaoqian
Highlights: Based on periodic region of dactyl club. The dactyl-inspired structure has excellent mechanical properties. It can be applied to many fields. Abstract: The periodic region of mantis shrimp's dactyl club, composed of the helicoidal arrangement of mineralized fiber, has excellent energy absorption and damage tolerance. This structure, inspired by the dactyl club, has been proved effective to improve the mechanical properties of composites. In this paper, a novel dactyl-inspired sandwich honeycomb (DSH) was fabricated with unidirectional carbon fiber and aluminum honeycomb based on the periodic region of the dactyl club. The DSH was compared with plain-woven skin sandwich-structural honeycomb (PSH) and unidirectional skin sandwich-structural honeycomb (USH) in tests of impact and bending. As a result, the average impact contact force of DSH was 3514.6 N, which was increased by 60.9% and 106.0% compared with PSH (2184.7 N) and USH (1705.8 N), respectively. The bending energy absorption of DSH was 29556.5 N·mm, which was increased by 278.3% and 115.4% compared with PSH (7812.2 N·mm) and USH (13719.6 N·mm), respectively. The results exhibited that the quasi-isotropic helicoidal arrangement of carbon fiber was an effective way to improve the impact resistance and bending energy absorption of DSH.